PELAKSANAAN PROGRAM INTEGRASI PPIA DENGAN PELAYANAN ANTENATAL CARE OLEH BIDAN DESA - ., Romdiyah; Nugraheni, Nazilla (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2019)
Data on HIV / AIDS cases from the Tegal District Health Office have increased from year to year. In September 2015 there were 436 HIV / AIDS cases consisting of 265 HIV cases, and 171 AIDS cases and 107 people who died. The importance of PPIA program integration with antenatal care services because many IRTs are affected by HIV / AIDS. The aim of the PPIA program is prevention HIV transmission from mother to child. The study aimed to analyze the factors that influence the implementation of program integration (PPIA) with antenatal care services by village midwives. This study is a quantitative study with a cross sectional approach. Data collection was carried out on 200 Village Midwives in the Tegal District area. Data analysis used univariate, bivariate, and multivariate analysis. The results showed that the variables related to the implementation of PPIA program integration with antenatal services were knowledge about HIV / AIDS in pregnant women, attitudes about HIV / AIDS in pregnant women and the availability of PPIA facilities. Multivariate results showed that the availability of PPIA facilities (p value = 0.003) is a variable that has the most significant influence on the implementation of PPIA program integration with an OR of 2.530. Suggestions To improve the early detection of all pregnant women at risk of HIV / AIDS including IMS and laboratory examinations when pregnant women make their first antenatal care visit. Keywords: Antenatal, PPIA